Bridge damage detection using reconstructed mode shape by improved vehicle scanning method. (15th July 2022) - Yang, D.S.; Wang, C.M.
Highlights: The kinks in the extracted mode shape directly pinpoint the damages without additional effort to construct any damage indices. The extracted higher mode shapes (i.e., second or third mode) provide better sensitivity in detecting the damage location. The improved VSM can identify multiple damage locations in the bridge with the use of two extracted higher mode shapes. Abstract: In this study, the improved vehicle scanning method (VSM) is adopted for structural health monitoring to identify healthy and damaged states of bridges. The improved VSM uses a designed elliptic filter (instead of the conventional Butterworth filter) to obtain the narrowband signals from the contact point response. These high-quality narrowband signals are able to furnish accurate vibration modes that reveal kinks that indicate the damage locations in the bridges. This improved VSM works best with a series of vehicles that are modeled as moving sprung masses passing over the bridge. The exciting vehicles modeled by heavier masses excite the bridge, and they are followed by a testing vehicle modeled by lighter masses to capture the acceleration response at the contact point. Some example problems involving bridges with different damage locations and severities were studied. It is shown herein that the improved VSM extracted mode shapes have very visible kinks to mark the damage positions of the bridges when compared to mode shapes extracted from existing VSMs. So, the improved VSM is able to directly pinpoint the damage locations from the extracted mode shapes with minimal postprocessing effort, whereas existing VSMs generally require additional effort, e.g., constructed damage indices, for damage identification. To better identify the damage locations, a few higher modes should be used so as to avoid missing the damage locations at nodes of a particular vibration mode.